APPLICATION OF CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL THROUGH THE USE OF AUDIO-VISUAL MEDIA TO ASSIST MATHEMATICS UNDERSTANDING IN FOURTH GRADE STUDENTS AT SDN 25 LUBUKLINGGAU - Eliya Lia; Agus Triyogo (Teaching and General Education Studies, 2026)
This study was motivated by the lack of meaningful learning experiences and low student enthusiasm in mathematics instruction, which led to low learning outcomes among fourth-grade students. The purpose of this study was to improve students’ mathematical understanding through the application of the Contextual Teaching and Learning (CTL) model assisted by audiovisual media. This study employed classroom action research consisting of two cycles and involved 12 fourth-grade students at SDN 25 Lubuklinggau during the odd semester of the 2025/2026 academic year. Data were collected through mathematics achievement tests and classroom observations and analyzed descriptively. The results showed a significant improvement in students’ learning outcomes. Classical mastery increased from 50% in Cycle I to 91% in Cycle II, exceeding the minimum mastery criterion of 85%. These findings indicate that the CTL model supported by audiovisual media effectively promotes active student participation and helps learners connect mathematical concepts with real-life contexts. In conclusion, the CTL model assisted by audiovisual media is effective in improving elementary students’ mathematical understanding. This study implies that teachers are encouraged to implement contextual and multimedia-based learning strategies. Future research is recommended to examine the application of this model in different grade levels or subject areas.